الرواية البوليسية الجزائرية: "خارج السيطرة" لـعبد اللطيف ولد عبد الله أنموذجا. - بثينة سليمي (My University, 2024)
Abstract: Literature is considered a reflective mirror of societal issues, and the detective novel has proven this, as its events and characters are linked to social reality, through which negative phenomena and the nature of human relations are monitored, the dimensions of which are embodied in events and their forms of violence and lawlessness, the spread of crime, and the manifestations and levels of deviance. Through our study of the novel “Out of Control” by the writer Abdellatif Ould Abdallah, which is considered as one of the literary genres in the Algerian detective novel, which shed light on various societal issues by unraveling the threads of two mysterious crimes and embodying the various characters of the novel in which the forces of good and the forces of evil struggle, in the words Other: A narration of the events that society suffers from in an interesting detective format. ---------------------- الملخص: يعتبر الأدب مرآة عاكسة لقضايا المجتمع والرواية البوليسية أثبتت ذلك حيث ارتبطت أحداثها وشخصياتها بالواقع الاجتماعي، والتي من خلالها يتم رصد الظواهر السلبية وطبيعة العلاقات الإنسانية التي تتجسد أبعادها في الأحداث وما فيها من أشكال عنف وخروج عن القانون، وانتشار الجريمة ومظاهر الانحراف ومستوياته . ومن خلال دراستنا لرواية" خارج السيطرة " للكاتب عبد اللطيف ولد عبد الله التي تعد كأحد الأجناس الأدبية في الرواية البوليسية الجزائرية، التي سلطت الضوء على قضايا المجتمع المختلفة من خلال فك خيوط جريمتين غامضتين وتجسيد مختلف شخصيات الرواية التي تتصارع فيها قوى الخير وقوى الشر، بعبارة أخرى سرد الأحداث التي يعانيها المجتمع في قالب بوليسي مشوق. ---------------- Résumé : La littérature est un miroir des enjeux de la société et le récit policier a prouvé que ses événements et personnalités sont liés à la réalité sociale, À travers lequel les phénomènes négatifs et la nature des relations humaines dont les dimensions se reflètent dans les événements et autres formes de violence et d’illégalité, la prévalence de la criminalité et les manifestations et les niveaux de délinquance sont surveillés. A travers notre étude du roman "Hors de contrôle" d’Abdelatif Oueld Abdallah, une course littéraire dans le roman policier algérien, qui a mis en lumière les différents enjeux de la société en dénonçant deux mystérieux fils du crime et en incarnant les différents caractères du roman dans lequel les forces du bien et les forces du mal, autrement dit, racontent les événements de la société sous une forme policière intéressante.
Keywords: detective novel - crime - detective - investigation; الرواية البوليسية-الجريمة- المحقق-التحقيق; détective novel-crime-investigateur-investigation.